Priorytety lokalnej polityki turystycznej - Nawrocka, Elżbieta (Priorities of Local Tourism Policy, 2007)
The objective of the hereby article is to identify local tourism policy priorities and means of their implementation based on the example of selected Lower Silesia districts. The study was based on the model of tourist policy which in Polish reality runs along the line: Europe (The European Union) - state - region - district - commune. Priorities resulting from this model, which should be carried out in district tourism policy include the construction of mutual relations between quality in tourism, sustainable development, public and private partnership and Tourist Economy Based on Knowledge, facilitating increased competitive attractiveness of regions at the tourist market. In practice, however, they are not carried out to their full potential. Among the priorities of district tourism policy there should be, most of all, included these activities which result in constructing tourism economy based on knowledge and developing public and private partnership. More attention should be devoted, in districts, to creating and upgrading the quality of tourist products.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 708-718